Effect of Aaker’s Model of Brand Personality on Customer Choice of Branded E-Retailing Outfits. - Patrick Kunle Ladipo; Ayodele Oniku; Janet Oluwasey Bankole; Olushola Solomon Akeke (TIJAB (The International Journal of Applied Business), 2022)
The current global pandemic has forced many customers to carry most of their purchases and other transactions to the virtual environment. The patronage of the online retailers will be affected by how they are perceived by the customers. It is on this basis that the researcher intends to study the effect of Aaker’s Model of brand personality on customer choice of branded e-retailing outfits. The researcher adopted a cross-sectional research design using the descriptive method to explain the analysis of the data administered. Primary data were gathered through online survey administered to the sample size of 397 undergraduate and postgraduate students of the University of Lagos, participating on a voluntary basis. However, 274 responses were fit and analysed using the Social Statistic package for Social Sciences (SPSS 20). The result revealed that four of the five dimensions of the Aaker’s model which are sincerity, excitement, competence and ruggedness have significant effect on consumers’ choice decision for electronic retailers while sophistication have no relationship whatsoever with customer choice of e-retailing outfits. The findings show that majority of University of Lagos students perceived Jumia to be competent, Jiji.Ng as rugged, Konga as competent, Olx.com.ng as rugged, SME Market Hub as competent, Slot.ng as competent, Obeezi as rugged and Payport as competent. Based on the findings, it is recommended that e-retailing outfits in order to sustain customer choice will need to improve on the four identified variables which are excitement, competence, ruggedness and sincerity to ensure sustainability.